PENERAPAN MODEL PEMBELAJARAN KONTEKSTUAL BERBANTUAN PROGRAM BANK SAMPAH UNTUK MENINGKATKAN HASIL BELAJAR PADA MATERI PEDULI LINGKUNGAN DALAM KEGIATAN KOKURIKULER IPAS SISWA KELAS V SD NEGERI 2 BEBALANG - Ni Nyoman Indriani; Nurul Isnaini Fitriyana; I Wayan Numertayasa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low level of understanding and poor learning outcomes among fifth-grade students at SD Negeri 2 Bebalang regarding the topic of environmental awareness, as well as the suboptimal utilization of the school's Waste Bank program in co-curricular Natural and Social Sciences (IPAS) learning activities. This Classroom Action Research (CAR) was conducted over two cycles based on the Kemmis & McTaggart model, comprising the stages of planning, action implementation, observation, and reflection. The results indicate that the implementation of the Contextual Teaching and Learning (CTL) model, supported by the Waste Bank program, successfully improved the execution of instruction from the "sufficient" category in Cycle I (84.38%) to the "very good" category in Cycle II (96.88%). Furthermore, the class average score rose from 78.24 (with a classical mastery rate of 70.59%) in Cycle I to 87.06 (with a classical mastery rate of 88.24%) in Cycle II, thereby exceeding the minimum success criterion of 80%. Thus, this approach proved effective in fostering meaningful learning and enhancing student learning outcomes.